Dynamic crushing response of closed-cell aluminium foams during shock loading - Islam, M.; Kader, M.; Hazell, P.; Escobedo-Diaz, J.; Brown, A.; Appleby-Thomas, G.; Saadatfar, M.; Quadir, Md Zakaria (2017)
Understanding the impact response of aluminium foams is essential for assessing their energy absorption capacity under dynamic loading. In this paper, the dynamic compaction behavior of closed-cell aluminium foam (CYMAT ™ ) has been tested using the plate-impact technique. Post-impacted samples have been examined using optical microscopy to observe the microstructural changes with the objective of elucidating the pore-collapse mechanism.